Fear Of Missing Out (Fomo) Among Generation Z Muslims In Medan City: The Perspective Of The Qur'an On Digital Lifestyle - Ayu Upairah Siagian; Fadhilah Is (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to explore the experiences of Generation Z Muslims in Medan City in dealing with the Fear of Missing Out (FoMO) phenomenon that arises due to the intensity of social media use in everyday life. Using an exploratory qualitative approach and phenomenological design, this study explores the subjective meaning given by respondents to digital social pressure and the internalization of Qur'anic values such as qana'ah, gratitude, and tawakkal as spiritual coping mechanisms. Data were collected through in-depth interviews with 20 participants and analyzed using thematic analysis methods. The results showed that FoMO manifested in the form of social anxiety, pressure to appear online, to feelings of envy and inferiority due to the culture of comparison on social media. However, the values of qana'ah and gratitude have been shown to provide inner peace and reduce the tendency to compare oneself, while tawakkal strengthens psychological and spiritual resilience. Respondents also developed digital-spiritual balance strategies through limiting online time, selecting positive content, and using social media as a means of preaching. This study concludes that Islamic values can be a foundation in forming personal digital ethics and reducing the negative impacts of social media. These findings encourage the development of a digital literacy curriculum based on Islamic spirituality as a response to the challenges of identity and mental health in the digital era.